Gastroduodenal fistula – a myth or reality - Bansod, Atish N.; Nagare, Akshay; Singh, Aryant Pratap; Agrawal , Anshu (International Surgery Journal, 2025)
Gastroduodenal fistulas are uncommon complications of peptic ulcer disease, and those involving the distal duodenum are particularly rare today. We describe an elderly man with a history of alcohol use and prior abdominal surgery who presented with longstanding upper abdominal pain, recurrent bilious vomiting, and significant weight loss. Evaluation revealed a fistulous tract between the posterior stomach and the fourth part of the duodenum, along with duodenojejunal narrowing. Definitive surgical management involved excision of the tract and reconstruction with Roux-en-Y gastrojejunostomy and duodenojejunostomy, leading to a satisfactory outcome.